ادارة الازمات في النؤسسة الاقتصادية - فيداء, شتحونه; اماني, بله باسي; اسلام, بوشول (unuversity of eloued- جامعة الوادي, 2023)
"هدفت هذه الدراسة إلى التعرف على واقع ودور إدارة الأزمات في المؤسسات الاقتصادية, تتضمن الدراسة عرضا نظريا متعلقا بالأزمات وتصنيفاتها وكيفية مواجهتها من خلال تطبيق مفهوم إدارة الأزمة , حيث أجريت الدراسة الميدانية في مؤسسة اتصالات الجزائر بولاية الوادي وشركة التأمين la carr , وذك باستخدام المقابلة لجمع المعلومات والبيانات المتعلقة بإدارة الأزمات وبعد تحليل المعلومات والبيانات توصلت الدراسة إل العديد من النتائج من أهمها : . أن تكون المؤسسة مهيأة بالتعامل والاستجابة للازمة بتداعياتها المختلفة. . وضع خطط تسمح للمؤسسة التنبؤ والتحكم والاستجابة لمواجهة الأزمات الممكنة . . ضرورة القيام بدور تكوينية لمسؤول إدارة الأزمة لتدريب عمالها للاستعداد لمواجهة أزمة ما. . العمل بفريق مختص يعمل على البحث على مجالات وطرق التعامل الأزمة ووضع خطة عمل سريعة محكمة ومدروسة بدقة من أجل إدارتها. . إن إدارة الأزمة يجب أن تكون فرصة لاكتساب الخبرة والتعلم للمؤسسة. " "This research aims to establish the reality and relevance of crisis management inside economic institutions. It entails offering a theoretical explanation on crises, as well as their classification and the tactics used to tackle them via the execution of the crisis management concept. To carry out this research, a field investigation was carried out at the Algerian telecoms institution in El Oued State, as well as at the insurance business La Carr, using the interview procedure to acquire essential information and data on crisis management. Following the analysis of the gathered information and data, the research came to various findings, the most noteworthy of which are: The institution should be ready to deal with and respond to the crisis's varied ramifications. Create strategies that will help the company to forecast, control, and respond to any emergencies. The requirement for crisis management authorities to play a formative role in training their employees to prepare for an emergency. Work with a trained team to examine the regions and techniques of dealing with the problem and to produce a speedy, well-thought-out action plan for handling it. Crisis management should be used to develop experience and knowledge for the organization."
Keywords: الازمة .ادارة الازمات .المؤسسة الاقتصادية; Crisis, crisis management, economic institution, insurance company, Algeria Telecom Company.